Emotional factors in advertising via mobile phones - Park, Taezoon (2013)
Advertising delivered via mobile phones constitutes a promising approach to marketing because it enables easy targeting, content personalization, and interactive communication. We conducted a laboratory experiment with 48 participants using a 24-item structured questionnaire about important emotional components involved in using mobile phones for advertising. The data revealed 3 factors that explained 63% of the total variance. Factor 1 included activation, restfulness, desire, affection, gratitude, and urgency. Factor 2 included anger, fear, sadness, and irritation. Factor 3 included skepticism and boredom. Stepwise multiple regression analysis indicated that boredom accounted for 45% of the variance in attitudes toward the advertisements. These findings imply that low-intensity negative feelings are important contributors to the success of advertisements presented on mobile phones and that engagingness is the most important emotional component in effective cell phone advertising.